Semi Aquatic Top-Predators as Sentinels of Diversity and Dynamics of Pesticides in Aquatic Food Webs: The Case of Eurasian Otter (Lutra lutra) and Osprey (Pandion haliaetus) in Loire River Catchment, France - Charles Lemarchand; René Rosoux; Philippe Berny (IntechOpen, 2011)
None